2010
DOI: 10.1016/j.nedt.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Surfing or still drowning? Student nurses’ Internet skills

Abstract: SummaryA study into student nurses' ability to use the Internet was published in Nurse Education Today in 2004. This paper repeats the research with a cohort of students starting their pre-registration programme in a UK university in 2007.In 2004 students were reported as having poor internet skills, and as not being frequent users of the Internet. In this study students were found to have significantly better ability to carry out basic tasks and significantly higher levels of internet use. Their ability to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
2
10
0
Order By: Relevance
“…In comparison to other groups, healthcare learners are late recipients of teaching and learning for ICT, computers and computing. Established and more recent literature shows that nursing students have been caught up in the aftermath of an underprepared workforce (Willmer , Bond & Procter , Bond , Sheikh et al . , Cheng ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other groups, healthcare learners are late recipients of teaching and learning for ICT, computers and computing. Established and more recent literature shows that nursing students have been caught up in the aftermath of an underprepared workforce (Willmer , Bond & Procter , Bond , Sheikh et al . , Cheng ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other groups, healthcare learners are late recipients of teaching and learning for ICT, computers and computing. Established and more recent literature shows that nursing students have been caught up in the aftermath of an underprepared workforce (Willmer 2005, Bond & Procter 2009, Bond 2010, Sheikh et al 2011, Cheng 2012. Collaborations between industry and higher education for workforce ICT preparation commenced circa 1970 with proactive global investment into workforce learning and development (Postle 1993, David & Foray 1994, Dummort & Dryden 1997, Schoenecker & Cooper 1998, Lamb et al 2002, Royal Society 2012, World Bank 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they proposed that educators may sometimes fail to help make the connection between the skills and experiences students have and they may not actually realise the students have the skills expected. A similar study by Bond (2010) comparing undergraduate nurses' ability in 2004 and 2007 revealed increased basic skills, however, the ability to carry out more complex tasks did not improve over the years. Langley (2012) stated that although students may be labeled "digital natives", these students may not know how to employ technology-based tools strategically to optimize learning experiences in university settings.…”
Section: Students and Ict Skills: A Review Of Literaturementioning
confidence: 84%
“…It was observed that 12.6% reported a very good knowledge of personal computer usage, 30.0% had a good knowledge, 27.4% had sufficient knowledge, while 24.8% had a beginner's knowledge. The findings from a study conducted by Bond [32] found that 30.8% of respondents viewed themselves as internet experts in 2001, this number increasing to 40% in 2007. Of the 54.4% who viewed themselves as Good at using the internet in 2001, the number increased to 53.4% in 2007.…”
Section: Discussionmentioning
confidence: 99%